Effective therapeutic communication knowledge of professional dental program students - Sari, Meity Karina; Yubiliana, Gilang; Suryanti, Netty (Universitas Padjadjaran, 2014)
Introduction: World Health Organization (WHO) declared the ultimate goal of medical education is to produce the five-star doctor, that doctor as a care provider, decision maker, manager, community leader, and communicator. Effective therapeutic communication can be learned and trained mainly on the professional program students. The purpose of this research was to obtain the data and information about effective therapeutic knowledge of professional communication dental program students. Methods: This research was a descriptive research with survey techniques. The sampling methods was simple random sampling from the questionnaire on 132 respondents. Results: The results of this research from the questionnaire shows the average level of effective therapeutic communication professional knowledge at student’s program in Dental Hospital Faculty of Dentistry Universitas Padjadjaran is 85%, 56% and classified as good level. Conclusion: Effective therapeutic knowledge of professional communication dental program students relatively good.